Not all little brown frogs are the same: a new species of secretive and cryptic Gephyromantis (Anura: Mantellidae) from Madagascar - Vieites, David R.; Wollenberg, Katharina C.; Vences, Miguel (Zootaxa, 2012)
We describe a new species of small diurnal frog of the genus Gephyromantis from Mahasoa, a fragment of mid-altituderainforest in the northern central east of Madagascar, located to the north east of Lake Alaotra. Analysis of DNA sequencesof the mitochondrial 16S rRNA and cytochrome b genes and of the nuclear Rag 1 gene indicate that Gephyromantis mafysp. nov. is closely related to G. eiselti and G. thelenae, that it is genetically distinct and when compared with the geneticdiversity of all species in the genus shows genetic differences similar to other pairs of species. These three species aremorphologically almost indistinguishable but the new species differs by a relevant and consistent genetic divergence inall markers studied, and by its advertisement calls composed of note series. The call is intermediate between G. eiselti andG. thelenae, showing shorter note duration and higher repetition rate than in G. thelenae and slightly longer note durationbut lower repetition rate than in G. eiselti. The new species is known only from Mahasoa forest but due to its secretivehabits and cryptic morphology, we assume that it is more widespread in the mid-altitude rainforests east and north of Lake Alaotra that so far have been very poorly surveyed. We propose a Red List status of Data Deficient for the new species.